2010
DOI: 10.1002/mrm.22596
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced MRI of neuroendocrine hepatic metastases: A feasibility study using a dual‐input two‐compartment model

Abstract: Neuroendocrine hepatic metastases exhibit various contrast uptake enhancement patterns in dynamic contrast-enhanced MRI. Using a dual-input two-compartment distributed parameter model, we analyzed the dynamic contrast-enhanced MRI datasets of seven patient study cases with the aim to relate the tumor contrast uptake patterns to parameters of tumor microvasculature. Simulation studies were also performed to provide further insights into the effects of individual microcirculatory parameter on the tumor concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 28 publications
0
52
0
Order By: Relevance
“…However, the interstitial compartment (EES) may have a larger radial dimension (compared with its axial dimension) without a radial concentration gradient, and can be regarded as largely homogeneous. The impulse residue function for DP2 model can be given by two physiologic phases (63)(64)(65)(66)(67)(68)(69):…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the interstitial compartment (EES) may have a larger radial dimension (compared with its axial dimension) without a radial concentration gradient, and can be regarded as largely homogeneous. The impulse residue function for DP2 model can be given by two physiologic phases (63)(64)(65)(66)(67)(68)(69):…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…Also, by setting E or PS ¼ 0, the single-(vascular) compartment DP model, R DP1 (t), is simply given by R p (t). The physiological meaning of the two transport phases can be explained as follows (63)(64)(65)(66)(67)(68)(69). During the initial vascular transit phase 0<t<t p , R p (t) is a constant (unity) reflecting the fact that the total amount (100%) of tracer in the injected bolus is residing in the tissue, although a portion of the tracer could diffuse from the IVPS into EES.…”
Section: Distributed Parameter (Dp) Models and Variationsmentioning
confidence: 99%
“…DCE-MRI has been tested for PanNETs staging. Koh et al [75] found three different patterns of contrast enhancement for neuroendocrine hepatic metastases, with specific perfusional parameters. DCE-MRI is therefore potentially able to categorize metastases on the basis of their vascular characteristics, with prognostic and therapeutic consequences.…”
Section: Pancreatic Tumorsmentioning
confidence: 99%
“…Immediately after t cap , the tracer that was not extracted and remains in the vascular space exits through plug flow, which results in a sudden decrease in R(t). A more gradual decrease in R(t) follows as the extracted portion diffuses back into the vascular space and is cleared by blood outflow [1,12,[14][15][16]. For a weighted sum of N pathways, the number of discontinuities is repeated N times.…”
Section: ) Occurrence Of Discontinuities In R(t)mentioning
confidence: 99%